Assessment of mental health outcomes and associated factors among workers in community-based HIV care centers in the early stage of the COVID-19 outbreak in Mali - Luis Sagaon-Teyssier; Aliou Kamissoko; Adam Yattassaye; Fodié Diallo; Daniela Rojas Castro; Rosemary Delabre; Fabrice Pouradier; Gwenaëlle Maradan; Michel Bourrelly; Mamadou Cissé; Laurent Vidal; Bintou Dembélé Keïta; et al. (Elsevier, 2020)
Background and objectives: In Mali, the non-governmental association (NGO) ARCAD Santé PLUS launched the CovidPrev program in response to the COVID-19 outbreak to ensure continuity of HIV care-related activities. This study aimed to identify individual and structural factors associated with mental health disorders (MHD) in the NGO's healthcare workers (HCW) in the early stage of the outbreak. Methods: Data were collected between April 6 and 11, 2020 for 135 HCW in ARCAD Santé PLUS's 18 community-based HIV care centers. Outcomes corresponded to the PHQ-9, GAD-7 and ISI instruments for depression, anxiety and insomnia, respectively. A general mixture model with a negative binomial distribution was implemented. Results: Most HCW were men (60.7%) and median age was 40 years IQR[33-46]. Symptoms of depression, anxiety and insomnia were declared by 71.9, 73.3, and 77% participants, respectively. Women were at greater risk of MHD. A lack of personal protection equipment and human resources, especially nurses, was associated with a high risk of MHD. Conclusions: Health policy must place non-front line HCW, including those in NGOs, at the core of the healthcare system response to the COVID-19 outbreak, as they ensure continuity of care for many diseases including HIV. The efficacy of public health strategies depends on the capacity of HCW to fully with and competently perform their duties.